PENGARUH MEDIA VIDEO PEMBELAJARAN TERHADAP MINAT BELAJAR SISWA KELAS IV PADA MATERI SOSIAL BUDAYA - Priyono Tri Febrianto; Jumiyati; Inggrid Adithalia; Warosatul Amalia; Mohassin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using instructional video media on students’ interest in learning social studies in elementary school. The background of this research is the low interest of students in social studies learning due to monotonous teaching methods. This research uses a quantitative approach with an experimental method. Data collection techniques include observation, questionnaires, and documentation. The results show that the use of video learning media has a positive and significant effect on students' learning interest. Students become more active, enthusiastic, and able to understand the material better. Therefore, video-based learning media is effective in increasing students’ interest in learning social studies in elementary schools.